Are there Risks from Nanocomposite Restoration Grinding for Dentists? - Pelclova, Daniela; Bradna, Pavel; Lischkova, Lucie; Zdimal, Vladimir; Maskova, Ludmila; Klusackova, Pavlina; Kolesnikova, Viktoriia; Ondracek, Jakub; Schwarz, Jaroslav; Pohanka, Miroslav; Navratil, Tomas; Vlckova, Stepanka; et al. (International dental journal, 2025)
OBJECTIVES: To evaluate the effect of short-term inhalational exposure to nanoparticles released during dental composite grinding on oxidative stress and antioxidant capacity markers. MATERIALS AND METHODS: Twenty-four healthy volunteers were examined before and after exposure in dental workshop. They spent 76.8 ± 0.7 min in the testing room during grinding of dental nanocomposites. The individual exposure to aerosol particles in each participant´s breathing zones was monitored using a personal nanoparticle sampler (PENS). Exhaled breath condensate (EBC), blood, and urine samples were collected pre- and post-exposure to measure one oxidative stress marker, i.e., thiobarbituric acid reactive substances (TBARS), and two biomarkers of antioxidant capacity, i.e., ferric-reducing antioxidant power (FRAP) and reduced glutathione (GSH) by spectrophotometry. Spirometry and fractional exhaled nitric oxide (FeNO) were used to evaluate the effect of acute inhalational exposure. RESULTS: Mean mass of dental nanocomposite ground away was 0.88 ± 0.32 g. Average individual doses of respirable particles and nanoparticles measured by PENS were 380 ± 150 and 3.3 ± 1.3 μg, respectively. No significant increase of the post-exposure oxidative stress marker TBARS in EBC and plasma was seen. No decrease in antioxidant capacity biomarkers FRAP and GSH in EBC post-exposure was seen, either. Post-exposure, conjunctival hyperemia was seen in 62.5% volunteers; however, no impairment in spirometry or FeNO results was observed. No correlation of any biomarker measured with individual exposure was found, however, several correlations with interfering factors (age, body mass index, hypertension, dyslipidemia, and environmental pollution parameters) were seen. CONCLUSIONS: This study, using oxidative stress biomarker and antioxidant capacity biomarkers in biological fluids of volunteers during the grinding of dental nanocomposites did not prove a negative effect of this intense short-term exposure. However, further studies are needed to evaluate oxidative stress in long-term exposure of both stomatologists and patients and diverse populations with varying health statuses.
Keywords: Nanocomposites; inhalační expozice; Oxidative Stress; Occupational Exposure; Dental nanocomposite; Nanoparticles; Breath Tests; oxidační stres; Humans; nanokompozity; Dentists; Thiobarbituric Acid Reactive Substances; Inhalation Exposure; Female; mladý dospělý; dospělí; oxid dusnatý; Respiratory function test; Occupational lung disease; lidé; Biomarkers; Antioxidants; dechové testy; Nitric Oxide; Glutathione; Exhaled airway markers; antioxidancia; Adult; ženské pohlaví; biologické markery; Male; pracovní expozice; zubní lékaři; nanočástice; glutathion; Young Adult; mužské pohlaví; látky reagující s kyselinou thiobarbiturovou